Are surveys blind to sexual and gender diversity? Reflections and an open proposal - Royo, Raquel; Aristegui, Iratxe; Silvestre, Maria (Frontiers in Psychology, 2024)
This article presents an open proposal on how to include questions that capture different gender identities and sexual orientations in quantitative research. Our theoretical framework is feminist theory and the evolution of feminist debates on identity categories, where the introduction of an intersectional gender perspective has been an important paradigm shift. We have compiled different previous categorization proposals and consider the consequences of not including categories that reflect identity diversity in surveys in order to finally offer our proposal for operationalizing identities. The proposal aims to ensure comparability in longitudinal studies and, at the same time, to incorporate new identity frameworks and an intersectional perspective in quantitative methodology research.